2015
DOI: 10.3390/nu7125508
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Low Quality Protein Diet Alters Plasma Amino Acid Concentrations of Weaning Rats

Abstract: Several studies have indicated the influence of a maternal low protein diet on the fetus. However, the effect of a maternal low quality protein diet on fetal growth and development is largely unknown. Wistar rats (11 weeks old) were mated and maintained on either a chow diet with 20% casein (n = 6) as the control group (C), or a low quality protein diet with 20% wheat gluten (n = 7) as the experimental group (WG) through gestation and lactation. Maternal body weights were similar in both groups throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
1
10
1
Order By: Relevance
“…31 Our previous study reported a novel set of data which showed that plasma methionine, glutamine and lysine were significantly lower and aspartic acid, ornithine and glycine-proline were significantly higher without an effect on birth weight in 3-week-old offspring exposed to maternal low-quality protein diet during gestation and lactation. 26 The metabolic phenotype that is related to the progression of chronic diseases is still largely unknown, but recent studies have introduced the hypothesis, that insufficiency in essential amino acids during critical periods of growth may limit certain metabolic set-points essential for maintained a healthy growth and organ developmental trajectory. 32,33 One of the most apparent postnatal effects of offspring exposed to maternal low-protein diets is altered body weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…31 Our previous study reported a novel set of data which showed that plasma methionine, glutamine and lysine were significantly lower and aspartic acid, ornithine and glycine-proline were significantly higher without an effect on birth weight in 3-week-old offspring exposed to maternal low-quality protein diet during gestation and lactation. 26 The metabolic phenotype that is related to the progression of chronic diseases is still largely unknown, but recent studies have introduced the hypothesis, that insufficiency in essential amino acids during critical periods of growth may limit certain metabolic set-points essential for maintained a healthy growth and organ developmental trajectory. 32,33 One of the most apparent postnatal effects of offspring exposed to maternal low-protein diets is altered body weight.…”
Section: Discussionmentioning
confidence: 99%
“…The full experiment which generated the offspring has been previously published. 26 The experiments were performed under the license from the Ethics Committee of Hacettepe University, Ankara, Turkey, number: 2014/17. All animals were housed individually in plastic cages and subjected to a 12 h light-dark cycle at a temperature of 20-22°C and 45% humidity.…”
Section: Animals and Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible explanations for these results include differences in the amino acid composition of proteins. Kabasakal et al (2015) have suggested that a maternal low-quality protein diet caused differences in plasma amino acid concentrations in weaning rats. Our previous studies have provided the first evidence of the negative effects of an amino acid deficiency on hyaluronan synthesis in human dermal fibroblasts (Yamane et al, 2016).…”
Section: Increased Hyaluronan Synthesis Is Associated With Has2mentioning
confidence: 99%